Some aspects of ion-acoustic whistlers in the ionosphere in the presence of negative ions - A. K. Sur; G. C. Das; B. Chakraborty; S. N. Paul; L. Debnath (International Journal of Mathematics and Mathematical Sciences)
A study is made of the propagation of ion-acoustic whistlers in the atmosphere including the effects of negative ions. The dispersion relation, phase and group velocities of whistlers are discussed. It is shown that the presence of negative ions introduces a critical frequency which, for equal ionic masses, is equal to the ion-cyclotron frequency. Special attention is given to the group travel time of whistlers at mid-latitude and equator so that the role of negative ions on the group travel time can be determined. The cyclotron damping of whistlers in the presence of negative ions has been studied. The velocity distribution, total attenuation and the induced magnetic field are calculated from the temporal as well as spatial cyclotron damping. It is suggested that the attenuation of whistlers may cause heating of the ionosphere. It is also indicated that the measurement of the group travel time from its source to the observer at the satellite would help to diagnose the ionospheric parameters. The results of the analysis are presented by several graphical presentations.